Information systems outsourcing in major Portuguese companies - contracting services - Fraga, Maria Glória (2012)
The information systems outsourcing presents itself as a strategic option for companies and continues to evolve in size and in type of contracts.In order to identify the most frequently outsourced services and aiming to get a better comprehension on the hiring process, a study was made based on a survey sent to information systems managers of large Portuguese companies.The study allowed to identify the information systems services usually outsourced, the main criteria used for selecting suppliers, the aspects considered in contracts, the difficulties that arise in relationships between customers and suppliers, and the mechanisms adopted for conflict resolution.